POSITIVE PSYCHOLOGICAL CAPITAL AND AUTHENTIC LEADERSHIP: A STUDY WITH MANAGERS OF PUBLIC AND PRIVATE ORGANIZATIONS IN BRAZIL (Editora Impacto Científico, 2025)
This study investigated the relationship between authentic leadership and positive psychological capital at work among leaders of public and private organizations in Brazil. A total of 136 managers participated, distributed across all states, mostly men (75%), with an average age of 42.9 years and an average of 12 years in leadership positions. Validated scales of Authentic Leadership and Positive Psychological Capital were applied, both showing satisfactory internal consistency (α > 0.70). The results indicated positive and significant correlations between authentic leadership and positive psychological capital, both in leaders’ self-perception and in relation to their direct leaders. Mediation analysis revealed that positive psychological capital acts as a mediating variable between the authentic leadership of leaders and that of their immediate superiors. Overall, higher levels of authentic leadership were associated with higher levels of positive psychological capital at work, highlighting the relevance of these constructs for well-being and organizational performance.